Inventarisasi Kumbang Koksi pada Tanaman Jeruk di Desa Indralaya Utara, Desa Indralaya Mulia, dan Desa Pemulutan, Kabupaten Ogan Ilir - Darmawan, Arif Rizky; Rani, Alfita; Hanif Hawari, Muhamad; Nurhaliza, Siti; Zuhri, Sya’bani; Nainggolan, Yulina Adelina; Pratama, Wahyu (Seminar Nasional Lahan Suboptimal, 2022)
Darmawan AR, Rani A, Hawari MH, Nurhaliza S, Zuhri S, Nainggolan YA, Pratama, W. 2022. Inventory of the koksi beetle on citrus plants in north Indralaya Village, Indralaya Mulia Village, and Pemulutan Village, Ogan Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 489-494. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In citrus plants, the koksi beetle acts as a natural enemy for pests, they will eat insects such as aphids, caterpillars, and other plant-destroying insects. This study aimed to inventory the species of koksi beetle in Indralaya Mulia Village, Pemulutan Village, North Indralaya Village, Ogan Ilir Regency. The method carried out in this observation uses a random survey method which is carried out by direct observation. The results showed that the koksi beetle in the first, second and third fields were different in each observation, the koksi beetle found on citrus plants, namely Coleomagilla macullata, Coccidulinae, Novius cardinalis, was found on the leaves and also on the young twigs, namely below the surface. leaves, the data used using primary data and secondary data. Secondary data were obtained from literature reference sources. While the primary data obtained from observations in the field. The data obtained will be presented in the form of a table. So the population of the koksi beetle in the three villages has different species, this is influenced by the presence of abiotic and biotic factors that are around the land. To find out more detailed data from the koksi beetle on citrus trees, an inventory of the koksi beetle can be used.